Clinical Profile, Outcome and Risk Factors for Mortality of Neonates Requiring Mechanical Ventilation at Tertiary Care Centre of Central Gujarat, India - Thakkar, Pareshkumar A; Pansuriya, Himanshu G; Bharani, Sheela; Taneja, Khushboo Kamal (Journal of Nepal Paediatric Society, 2021)
Introduction: Mechanical ventilation is an important factor contributing to the reduced neonatal mortality in NICU. However, many ventilated babies are left with detrimental sequelae. This study was undertaken to know the prognostic predictors and survival outcome in the ventilated neonates. We assessed the clinical profile, outcome of mechanical ventilation and analysed the risk factors for mortality and complications resulting from mechanical ventilation. Methods: A prospective study was conducted at the NICU of a tertiary care hospital in India. The study period was from May 2015 to April 2016. Neonates who underwent mechanical ventilation and met the inclusion criteria were enrolled in the study. Their demographic profile, outcomes and risk factors were documented and analysed using appropriate statistical methods. Results: 285 neonates required mechanical ventilation during the study period. Among them, 190 were included in the study. Overall mortality was 99 out of the 190 enrolled (52%). The most common indications for mechanical ventilation were Respiratory Distress Syndrome (RDS), Meconium Aspiration Syndrome (MAS) and apnea. Risk factors contributing significantly to higher mortality of ventilated neonates were very low birth weight (VLBW), gestation of less than 32 weeks, shock, ventilator- associated complications like pneumothorax and pulmonary haemorrhage. In multiple regression analysis, very low birth weight, circulatory disturbances, pneumothorax, pulmonary haemorrhage, and higher initial FiO2 requirement were found to be independent risk factors of mortality. Conclusions: The commonest indications for mechanical ventilation were RDS and MAS. Significantly higher mortality was seen amongst VLBW, preterm neonates. Co-morbidities like circulatory disturbance, and complications like pneumothorax and pulmonary haemorrhage contributed to adverse outcomes.